Plasma and erythrocyte cholinesterase activities and values of some plasma parameters in subjects with different body weight - Gokcen, Mursel; Gokbel, Hakki; Kaptanoglu, Bunyamin; Buyukbas, Sadik; Ucok, Kagan; Vural, Huseyin; Cigli, Ahmet (Annals of Medical Research, 2021)
None